Pesticide Toxicity Profile: Ethylenebis (dithiocarbamate) Pesticides - Frederick M. Fishel (EDIS, 2005)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of ethylenebis (dithiocarbamate) (EBDC) pesticides used as fungicides registered for use in Florida. This document is PI-64, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2005.